Considerations for the management of home parenteral nutrition during the SARS-CoV-2 pandemic: A position paper from the Home Artificial Nutrition and Chronic Intestinal Failure Special Interest Group of ESPEN. Issue 7 (July 2020) - Lal, Simon; Van Gossum, Andre; Joly, Francisca; Bozzetti, Federico; Cuerda, Cristina; Lamprecht, Georg; Mundi, Manpreet S.; Staun, Michael; Szczepanek, Kinga; Wanten, Geert; Wheatley, Carolyn; Pironi, Loris; et al.
Summary: The management of patients with chronic intestinal failure requiring home parenteral nutrition has been and will continue to be impaired during the SARS-CoV-2 pandemic. Multidisciplinary intestinal failure teams may have to adapt their clinical approaches to home care, outpatient care as well as hospital admission and discharge in order to keep this vulnerable group of patients as safe and well as possible during the unprecedented challenges that countries are facing during the pandemic. Equally, it is important that expert advice from intestinal failure teams is available when home parenteral nutrition (HPN)-dependent patients require admission with SARS-CoV-2 infection. The Home Artificial Nutrition & Chronic Intestinal Failure Special Interest Group of the European Society for Clinical Nutrition and Metabolism (ESPEN) has developed a position paper to outline areas for intestinal failure teams to consider when managing patients with chronic intestinal failure during the SARS-CoV-2 pandemic.